2009
DOI: 10.1590/s0100-06832009000500025
|View full text |Cite
|
Sign up to set email alerts
|

Resposta do arroz irrigado ao suprimento de amônio e nitrato

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
2
12
0
5
Order By: Relevance
“…These results are similar to those reported by Holzschuh et al (2009), who indicated differences between genotypes with respect to their ability to take up and accumulate N in the form of nitrate in shoots.…”
Section: Experiments II (Calcium Nitrate)supporting
confidence: 92%
See 1 more Smart Citation
“…These results are similar to those reported by Holzschuh et al (2009), who indicated differences between genotypes with respect to their ability to take up and accumulate N in the form of nitrate in shoots.…”
Section: Experiments II (Calcium Nitrate)supporting
confidence: 92%
“…D'Andrea et al (2004) and Santos et al (2011) have also reported that nitric N is important for initial growth. There is a hypothesis for different responses by distinct rice genotypes to N-NO 3 -and N-NH 4 + supply, and related studies are generally performed using a nutrient solution (ARAÚJO et al, 2012) or flooding (HOLZSCHUH et al, 2009). Therefore, the aim of this study was to evaluate the agronomic efficiency of nitrogen rates, nutrient absorption, and initial growth of upland rice genotypes originating from Brazil and Colombia when fertilized with nitric or ammoniacal sources.…”
Section: Introductionmentioning
confidence: 99%
“…Arf et al (2001), Bordin et al (2003), Cazetta et al (2008) and Pacheco (2009) also obtained higher upland rice yield using millet as cover crop. This can be attributed to a better development of upland rice with low nitrate/ammonium ratio, in the first weeks of crop development (Lin et al, 2005;Li et al, 2007;Holzschuh et al, 2009;Poletto et al, 2011;Araújo et al, 2012). Millet provided the lowest amount of nitrate and the highest level of ammonium to the soil in almost all evaluations.…”
Section: Resultsmentioning
confidence: 91%
“…Araújo et al (2012) reported that upland rice plants have difficulty in metabolizing nitrate in the early development, since the production of nitrate reductase enzyme by this crop takes time to begin. This fact could explain the low initial rice development, when N-NO 3 -prevails in the environment, with negative effects on rice grain yield (Holzschuh et al, 2009), as observed in treatments with U. brizantha, U. ruziziensis and P. maximum. (1) Means followed by equal letters do not differ by LSD test, at 5% probability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation